Analysis of the Effectiveness of Tax Incentives on Energy Sector Investments - Sonjaya, Yaya; Noch, Muh Yamin (Advances in Taxation Research, 2024)
Purpose: This study examines the impact of tax incentives on investment in the energy sector, focusing on empirical evidence, theoretical framework, and policy implications. Research Design and Methodology: This research adopts a multi-perspective approach, utilizing empirical studies, theoretical insights, and practical considerations to analyze it comprehensively. Methodologically, the study synthesizes existing literature and integrates insights from economics, environmental science, and policy studies. Findings and Discussion: The findings suggest that well-designed tax incentive programs positively influence investment flows in the energy sector, especially in renewable energy projects. Policy stability and coherence are critical determinants of tax incentives' effectiveness, emphasizing the need for an integrated policy approach. Implications: The implications of these findings highlight the importance of collaborative action between policymakers, industry stakeholders, and researchers in driving effective energy transition strategies. Policymakers are encouraged to prioritize designing and implementing targeted incentive programs, while industry stakeholders are encouraged to engage in the policy formulation process actively. Researchers must continue studying the effectiveness of tax incentives and identify strategies to increase their impact on energy sector investment.